Tashawwurāt aṭ-Tullāb Hawla Fa‘āliyat Asālīb Tadrīs al-Lughah al- ‘Arabiyyah fī Madrasah Tsānawiyyah - Azka, Lulu; Naifah; Fauzia, Eva Lathifah; Saputri, Anggi Anggela; Maulana, Bayu Abi (Mantiqu Tayr: Journal of Arabic Language, 2026)
This study was motivated by the low motivation and negative perceptions of students towards Arabic language learning, which is still dominated by traditional methods and pays little attention to the affective aspects of students. The purpose of this study was to describe students' perceptions of the effectiveness of teaching methods in Arabic language learning at Madrasah Tsanawiyah Fatahillah Semarang and to identify the factors that influence it. This study used a descriptive quantitative approach with data collection through a four-level Likert scale questionnaire administered to 20 eighth-grade students. The results showed that students' perceptions were in the good category with an average score of 2.98. The indicators of clarity of delivery, variety of methods, and student participation received the highest scores (3.08), while the relevance and contextuality of the material were still the weakest aspects (2.75). In conclusion, teachers have applied quite effective methods, but there needs to be improvement in context-based and real-life learning. Scientifically, this study contributes to strengthening Arabic pedagogy studies by emphasizing the dimensions of student perception and motivation. It is recommended that future studies use a mixed methods approach to explore in greater depth the relationship between perception, motivation, and student learning outcomes.